Verbal Communication of Schizophrenic Patients Due to Neurotransmitter Distortion - Siregar, Iskandarsyah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to analyze the verbal communication of adult schizophrenics who develop due to neurotransmitter distortion. The qualitative descriptive method of a case study is used as a method of analysis by making psycholinguistic studies a foundation. Analysis of understanding of the meaning used in this research is to use pragmatic theory with the principle of cooperation (Grice's theory). Based on the analysis results obtained conversation data that verbals follow the principle of cooperation. Schizophrenic objects are able to respond and organize the stages of language production such as conceptualization, formulation, articulation, and self-monitoring, although they are not consistent.